THE ROLE OF MARKETING MANAGEMENT IN DEVELOPMENT CONCEPT BUSINESS DURING THE COVID-19 PANDEMIC - Sugiarti, Sri (Journal of Research in Construction, Communication, and Commercial, 2022)
During the COVID-19 pandemic, many business people have difficulty surviving and developing, so the role of marketing management is very much needed. Marketing management is the overall system of business activities aimed at planning, pricing, promoting, and distributing goods and services that satisfy needs to both existing and potential buyers. The formulation of the problem is: "What is the role of marketing management in conceptual business development during the covid-19 pandemic?". Looking for other business opportunities as other income besides the main income. Or with a marketing strategy through social media, namely the strategies taken to increase sales turnover in the business are: Create an online shop site, add networks and relationships, add interesting marketing content,